Potential and Tourism Development Strategy of Pasir Kuning Beach, Tempilang District, West Bangka Regency - Orian amin; Hastuti Hastuti (Eduvest - Journal of Universal Studies, 2026)
Pasir Kuning Beach in Tempilang District, West Bangka Regency has not yet attracted significant tourist interest, either from local residents or from visitors outside the region. Local residents tend to travel to other destinations outside Tempilang District, while tourists from outside the region prefer beaches located closer to the city center. In addition, the limited availability of tourism information on social media contributes to the low popularity of this tourist destination. Therefore, this research aims to analyze the tourism potential of Pasir Kuning Beach and tourism development strategies for the area. This research uses a qualitative approach, with data collected through observation and interviews with key informants. The data were analyzed using the Miles and Huberman interactive model and were complemented by a SWOT analysis to formulate tourism development strategies. The results show that Pasir Kuning Beach possesses several tourism potentials. In terms of attractions (something to see), the beach offers unique cultural events such as the traditional Ketupat War festival and distinctive yellow sand that forms its main natural attraction. In terms of activities (something to do), tourists can utilize existing facilities such as gazebos, photo spots, and recreational areas. However, several challenges remain, including the relatively remote location from the city center, limited transportation access, and incomplete tourism facilities. Based on the SWOT analysis, development strategies include preserving the Ketupat Warcultural tradition as a tourism attraction, promoting the uniqueness of the beach’s yellow sand, improving tourism facilities and accessibility, and strengthening promotional activities, particularly through digital and social media platforms.